Analisis Keamanan Data pada Aplikasi Chatting Menggunakan Metode Network Forensics - Reben Yulandra Agustian; Tata Sutabri (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
This study aims to analyze data security in popular chat applications using network forensics methods. This method enables the collection and analysis of data from networks to detect and understand potential threats or security breaches. In this research, several chat applications are analyzed to identify vulnerabilities that unauthorized parties could exploit. The results of this study are expected to provide a better understanding of the steps that can be taken to enhance data security in chat applications.